Pendampingan Pemasaran Produk Kopi Arabica Gayo Bersertifikasi Halal - Amri, Abrar; Putri, Cut Widy Aulia; Soufyan, Dara Angreka (Nawadeepa: Jurnal Pengabdian Masyarakat, 2024)
In the era of globalization, halal certification is an important factor in increasing the competitiveness of local products. Consumers awareness of the importance of consuming halal products has increased, and halal certification has become proof of product credibility. However, many local business actors, especially Gayo Arabica Coffee still experience difficulties in obtaining halal certification. This community service aims to market halal-certified Arabica Gayo Coffee for local business actors. The goal is to improve the competitiveness of Gayo Arabica Coffee in the domestic and global markets. This community service is carried out by socialization methods about the importance of halal certification, assistance in the halal certification registration process, facilitation of halal certification, coaching and training related to Halal Product Assurance System (HPAS) and marketing of halal-certified local products. This community service is expected to produce several results, including the business of Arabica Gayo Coffee to have their own halal certificates, increasing the competitiveness of Arabica Gayo Coffee in the domestic and global markets, increasing income and welfare of Arabica Gayo Coffee’s business actors, and increasing consumer trust in Arabica Gayo Coffee. This community service is an effort to increase the competitiveness of Arabica Gayo Coffee through marketing assistance for halal-certified Arabica Gayo Coffee. By increasing awareness and ability of Arabica Gayo Coffee’s business actors in obtaining halal certification, it is hoped that Arabica Gayo Coffee will be able to compete in the global market and improve community welfare.